Integrated care systems in England: the significance of collaborative community assets in promoting and sustaining health and wellbeing - Corrigan, Oonagh; Danielsen, Scott; Doherty, Shannon; Lane, Pauline (Frontiers in Sociology, 2024)
Until recently the healthcare system in England was based on a commissioning/provider model. However, this has been replaced with an Integrated Care Systems (ICSs) approach, aimed at improving health and wellbeing and reducing inequalities through local collaborative partnerships with public sector organizations, community groups, social enterprise organizations and other local agencies. Part of this new approach is an emphasis on the role of community assets (i.e., local resources), that are considered integral to promoting positive health and wellbeing outcomes. This paper presents research from a series of three research studies on “community assets” conducted in the East of England within a newly established ICS. Based on analysis of qualitative data highlighting the lived experience of community asset members, this paper shows the positive wellbeing impact on vulnerable community members that assets provide. Further insight on the local impact and the collaborative nature of the research is provided suggesting that new asset-based approaches recognize the social determinants of health. This presents a shift away from positivistic linear approaches to population health and wellbeing to a new non-linear collaborative approach to addressing health inequalities and promoting wellbeing. The authors suggest that exploring this through a complexity theory lens could illuminate this further. Finally, the authors warn that while community assets have an important role to play in empowering citizens and providing much needed support to vulnerable and disadvantaged communities, they are not a substitute for functioning funded public sector services that are currently being undermined by ongoing local governments funding cuts. As such, while community assets can help ameliorate some of the negative effects people experience due to economic, structural and health disadvantages, only a more fair and more equal distribution of resources can address growing health inequalities.